دور الرأسمال البشري في تحقيق القدرة الابتكارية لمؤسسة اقتصادية استطلاع رأي عمال مؤسسة رايلان للصناعة الكهرومنزلية_عنابة_ - صونية رزايقية (My University, 2023)
The study aims to evaluate the reality of preparing the basic requirements for human capital development in the Raylan Corporation active in manufacturing of electronic products and its relationship to achieving the innovative capacity of that company, through conducting a field study on a sample of 36 workers of the Raylan Company. The field study concluded that the Raylan Company invests acceptably in the requirements of human capital in a way that achieves a good innovation capacity that makes it able to succeed in the Algerian market. ........................................................ تهدف هذه الدراسة إلى تقييم واقع تحضير المتطلبات الأساسية لتنمية الرأس مال البشري في مؤسسة رايلان لصناعة الأجهزة الكهرومنزلية والإلكترونية وعلاقتها بتحقيق القدرة الابتكارية لتلك المؤسسة، وذلك من خلال إجراء دراسة ميدانية على عينة تقدر ب36 عاملا من عمال المؤسسة. توصلت الدراسة الميدانية إلى نتيجة مفادها أن مؤسسة رايلان تستثمر بشكل مقبول في متطلبات الرأس مال البشري بطريقة تحقق لها قدرة إبتكارية حسنة تجعلها قادرة على النجاح في السوق الجزائري. ....................................................... L'étude vise à évaluer la réalité de la préparation des exigences de base pour le développement du capital humain dans la Raylan Corporation, entreprise active dans la fabrication de produits électroniques, et sa relation avec la réalisation de la capacité d'innovation de cette entreprise, à travers la réalisation une étude de terrain sur un échantillon de 36 travailleurs de l’entreprise Raylan. L'étude de terrain a conclu que l’entreprise Raylan investit de manière acceptable dans les exigences du capital humain d'une manière qui atteint une bonne capacité d'innovation qui lui permet de réussir sur le marché algérien